Outcome of intraoperative use of mitomycin C combined with conjunctival auto graft in recurrent pterygium - Goswami, Manash Kumar; Hossain, F.; Shamsudduha, A.B.; Asaduzzaman, M (IMC Journal of Medical Science, 2017)
Background and objectives: Recurrent pterygium is an important ocular problem in our country. There are different modalities of treatment for recurrent pterygium. The present study was undertaken to determine the effect of intraoperative mitomycin C along with conjunctival auto graft to prevent recurrence of pterygium. Methods: Patients with recurrent pterygium attending a tertiary care hospital in Dhaka from January 2013 to June 2015 were included in the study. Cases were randomized into two groups. Group 1 had pterygium surgery with conjunctival auto graft and Group 2 had auto graft and intraoperative mitomycin C (0.02%). All cases were followed up for one year to assess recurrence of pterygium. Results: A total of 54 recurrent pterygia cases were included in the study. The age of study population was 25 to 65 years. The recurrence rate of pterygium after 12 months was 77.7% in group 1 and none in group 2. No major postoperative complication was observed. Conclusion: The study demonstrated that the use of intraoperative mitomycin C along with conjunctival auto graft had significant effect in preventing the recurrence of pterygium. IMC J Med Sci 2016; 10(2): 49-52